Peningkatan Pemahaman Uji Regresi dan Interpretasi Data Mahasiswa Melalui Pelatihan Software JASP - Syaharuddin Syaharuddin; Vera Mandailina; Nursina Sari; Dian Eka Maya Sari; Rosada Rosada; Sri Rejeki (Sekolah Tinggi Teknologi Industri (STTI) Bontang, 2022)
The regression test is one of the hypothesis tests that must be understood by students when analyzing research data. Therefore, the purpose of this activity is to increase students' understanding of the regression test process to make it easier for students to analyze research data. Participants were a research class group of 29 students. The speaker delivered an introduction to the material, then followed by direct practice by students including how to install JASP software, understand every feature that exists, input data, and perform data analysis. Activities were evaluated using a Likert scale questionnaire. Evaluation of activities showed that 76.01% of students understood regression test analysis techniques and how to use JASP software. In the future, we hope that students can develop their skills in data analysis even more in-depth.